Eksistensi Lembaga Adat Kota Jambi - Iman Hidayat (Jurnal LEX SPECIALIS, 2011)
Existence of Indigenous Institutions in the Regulation of the Minister of Interior No. 3 of 1997 as follows: Accommodating and channeling public opinion to the government and resolve disputes relating to customary law, Customs and habits of society in order to enrich the local culture and empower the community in supporting the implementation of the government, implementation of development and social development; create a democratic and harmonious relationship and objective between the Head of Indigenous / Stakeholder Indigenous Peoples or the Oldest and Leader / Indigenous leaders with government officials in the region. While the function of Customary Institutions in the Regulation of the Minister of Interior No. 3 of 1997 is to carry out data collection activities in order to develop policies and strategies to support the smooth governance, sustainable development and supports the success of the coaching community. Key Note : Existence of Traditional Institutions